Lack of glutamate neurotransmission in melanin-concentrating hormone neurons alters mouse reproduction and metabolism in a sex-specific manner - Bethany G. Beekly; Dania Zeidan; Wenicios F. Chaves; Jonah-Isabella Sta-Monica; Thomas Saunders; Cristina Saenz de Miera; Christian R. Burgess; Carol F. Elias (Biology of Sex Differences)
Plain language summary Melanin-concentrating hormone (MCH) is a neuropeptide important for the regulation of metabolism, sleep, circadian rhythms, and other body functions. MCH neurons contain the excitatory neurotransmitter glutamate, which is released via vesicular glutamate transporter 2 (VGLUT2). The release of glutamate from MCH neurons is known to play a role in metabolism in males, but its action in female physiology has not been determined. Furthermore, little is known about the role of glutamate release from MCH neurons in reproductive function. We developed a new transgenic mouse model that expresses Cre recombinase driven by the MCH gene (Pmch) and deleted Vglut2 from the MCH neurons. We then assessed reproductive and metabolic function in both sexes. Females exhibited late-onset leanness, delayed sexual maturation, and increased latency to pregnancy. On a high-fat diet, males showed improved insulin resistance, and both sexes displayed an improved daily pattern of food intake. These findings highlight the importance of considering sex as a relevant biological variable in MCH neuronal function.